Effectiveness of Teaching Program on Nurses’ Knowledge Concerning the Side Effects of Chemotherapy among Children with Leukemia at Oncology Wards in Baghdad City - Mohammed, asmahan; aburaghif, leila (Iraqi National Journal of Nursing Specialties, 2018)
Objective(s): to assess the effectiveness of educational program on nurses’ knowledge concerning the side effects of chemotherapy among children with leukemia. Methodology: A descriptive analytic (quasi – experimental) design study was carried out at Baghdad City from 2 nd of October to 27th of June 2015. Non-probability sample of (35) male and female nurses was selected from the Oncology Wards in Children Welfare, Child’s Central and Baghdad Teaching Hospital. The study instruments consisted of two major parts to meet the purposes of study. The first part is related to nurses’ demographic characteristics and the second part (four domains) is related to nurses’ knowledge concerning the side effects of chemotherapy. The researcher examined the nurses knowledge for each hospital alone by introducing the pre-test then, the teaching program of four lectures was given. Every day, a one – hour lecture was given. Afterward, the post-test. The data were analyzed by using two statistical approaches: Descriptive and Inferential statistics. Results: The study revealed that the general knowledge of nurses regarding side effects of chemotherapy was 45.7% (Good) for the post-test as opposed to the pre-test which was 51.4% ( acceptable). Recommendation: The study recommended that nurses should be encouraged to attend specific meetings, programs, workshops and seminars in concern of leukemia treatment and side effect of chemotherapy to be acquainted with the most recent, advances and skills in the field.